A new O3-type layered oxide cathode with high energy/power density for rechargeable Na batteries1. Issue 22 (18th March 2015) - Liu, Haodong; Xu, Jing; Ma, Chuze; Meng, Ying Shirley
<x xml:space="preserve">Abstract</x> A new O3–Na0.78Li0.18Ni0.25Mn0.583Ow is prepared as the cathode material for Na-ion batteries, delivering exceptionally high energy density and superior rate performance. No phase transformation happens through a wide range of sodium concentrations.